Differences in tennis serve kinematics between elite adolescent male and female players - Connolly, M.; Middleton, K.; Reid, M. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to compare kinematic differences in elite adolescent male and female tennis serves. A 3D motion capture system was used to capture whole body, racquet and ball toss kinematics while twenty elite adolescent tennis players (male = 10, female = 10) performed flat and kick serves. Females had greater vertical front hip velocity (FS: 0.2 m/s, KS: 0.2 m/s greater than males), whilst males experienced larger peak shoulder external rotation displacements in both flat (10° greater) and kick (8° greater) serves compared to females. Females tossed the ball higher (FS: 18 cm, KS 19 cm) whilst males impacted the ball more laterally (across the body) (FS: 17cm, KS: 12) and more forward (FS: 10 cm, KS: 13 cm) into the court. Females had greater lower body kinematics whereas males tended to rely on shoulder external rotation to produce ball speed.